Vicarious post-traumatic growth in Chinese oncology nurses: A cross-sectional study - Jinghan Xu; Dandan Chen; Blandine Lucrece Jongo Fouelefack; Yunxian Zhou (PLoS ONE, 2025)
In the traditional Chinese culture, vicarious trauma poses a significant threat to oncology nurses who are frequently exposed to death and illness. This exposure can undermine both the physical and mental health of these nurses, potentially affecting team retention. Vicarious post-traumatic growth, a positive outcome of trauma exposure, has been shown to mitigate the adverse effects of vicarious trauma. As a result, fostering vicarious post-traumatic growth is an important area of focus. However, the prevalence of vicarious post-traumatic growth and its influencing factors is limited. The relationship between vicarious post-traumatic growth and vicarious trauma also remains unclear. This study used a cross-sectional survey design. A total of 445 questionnaire were collected between October and December 2023, with 401 valid responses retained for analysis. Participants completed questionnaires that included demographic and work-related variables questionnaire, the Vicarious Trauma Questionnaire (VTQ) and the Chinese-Post Traumatic Growth Inventory (C-PTGI). Descriptive statistics, Pearson correlation analysis, t-tests or ANOVA (F-tests) and multiple regression analysis were conducted to investigate the level of vicarious post-traumatic growth and the modifiable factors among oncology nurses. Multicollinearity diagnostics confirmed no significant collinearity among variables. This study found that Chinese oncology nurses developed high levels of vicarious post-traumatic growth (n = 401,68.67 ± 18.88) based on medium levels of vicarious trauma (n = 401,66.32 ± 22.50). In the multiple regression analysis, vicarious trauma (B = −0.129, 95%CI −0.211 ~ −0.046), social support (B = 7.963, 95%CI 4.680 ~ 11.247), and job satisfaction (B = 7.418, 95%CI 5.444 ~ 9.391) were independently associated with vicarious post-traumatic growth. These findings have important implications for the future implementation of effective interventions to improve the level of vicarious post-traumatic growth. Recommendations include death education, emotional labor strategies training, mindfulness therapy, psychological counseling, and Balint groups, which can improve the level of vicarious post-traumatic growth in Chinese oncology nurses.